Construction of Self-Identity: “Blusukan” as the Strategy of Campaigning for Surakarta City Mayor Election - Gama, Betty; Sudardi, Bani; Abdullah, Wakit; Wijaya, Mahendra (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
In political communication, “blusukan” (impromptu visit) is called door to door campaign, in which candidates conduct face-to-face communication by visiting the people directly. This situation creates personal intimacy in the sense of there is no physical distance and formal protocolary distance. People can see the personality of their candidate leaders closely. This face-to-face communication meeting can be interpreted that the candidates